Social Support and Caregiving in Italy: The Specificities of Care Relationships - Tronca, Luigi; Stanzani, Sandro; Ferrucci, Fabio; Carradore, Marco (Italian Sociological Review, 2025)
Informal caregiving is an invisible component of familistic welfare regimes, where the burden of care is predominantly delegated to primary networks. Drawing on a structural interactionist perspective, this article presents findings from an Italian national survey of 1,504 adults, analysed through personal network methods to investigate how network morphology shapes caregiving practices. Caregivers (19.8% of the sample) assist older people, persons with chronic illnesses, or persons with disabilities. Results show that caregivers belong to larger and denser networks than non-caregivers, reflecting strong bonding capital typical of familistic contexts; however, they display lower betweenness and ego-centric density, signalling limited brokerage capacity and reduced access to bridging ties. This structural closure reinforces the “total social fact” nature of caregiving, where mixed tasks of physical and administrative care predominate. The most significant of these is the fact that for all types of frailty, over a quarter of carers say they have no one to support them in their caregiving activities. Despite a certain uniformity across caregiving profiles, differences emerge: disability care is embedded in cohesive, inward-looking networks associated with higher burden; chronic illness care mobilises more open networks and higher satisfaction; elder care remains rooted in normative familial obligations. Across conditions, over one quarter of caregivers report lacking any support, while dissatisfaction with formal services highlights a dualised care regime unable to compensate for weak bridging social capital. These findings underscore the need for policies that expand caregivers’ relational opportunities beyond primary networks. At the macro level, it does not seem necessary to distinguish policies by caregiver type. However, at the level of social intervention, it is considered appropriate to pay attention to some of the differences that emerged across the three profiles, such as the structure of their support networks, attitudes towards services, and respondents’ future projections in their role as caregivers.